Child-Protection Systems – Hungarian Perspective - Jakab, Nóra; Benyusz , Márta (Child-Protection Systems, 2025)
Abstract:Child protection is aimed at promoting the upbringing of children in the family, preventing and eliminating their vulnerabilities and providing substitute protection for children leaving parental or other care. In Hungary, the framework for child protection is laid down by Act LXIV of 1991 on the proclamation of the Convention of 20 November 1989, the Fundamental Law of Hungary, Act V of 2013 on the Civil Code, Act III of 1993 on social administration and social benefits, Act XXXI of 1997 on the protection of children and the administration of guardianship (Gyvt.) and other regulations. According to the Central Statistical Office, a significant number of children benefit from the child protection care system. The legal significance of the Gyvt. is being the first complete and independent legal regulation of child protection in Hungary. Moreover, its significance for child protection is that it adds new institutions and transforms and systematises the child protection system. When drafting the legislation, the legislator considered that a child protection system based on special intervention by the authorities should always be preceded by a child welfare system based on voluntary benefits. Keywords: principle, child protection benefit, child protection guardian, statistical data